Narrow‐ (3.0 mm) Versus Standard‐Diameter (4.0 and 4.5 mm) Implants for Splinted Partial Fixed Restoration of Posterior Mandibular and Maxillary Jaws: A 5‐Year Retrospective Cohort Study. Issue 4 (1st April 2017) - Pieri, Francesco; Forlivesi, Caterina; Caselli, Ernesto; Corinaldesi, Giuseppe
Abstract : Background: Evidence concerning predictability of narrow‐diameter implants (NDIs) (<3.3 mm) to restore partially edentulous posterior maxillary and mandibular areas is limited. The aim of this study is to compare the 5‐year outcomes of NDIs (3.0 mm) and standard‐diameter implants (SDIs) (4.0 to 4.5 mm) supporting fixed partial dentures (FPDs) in posterior mandibular and maxillary jaws. Methods: All patients treated with at least two adjacent NDIs or SDIs according to available bone thickness and with a minimum follow‐up of 5 years after placement were invited to undergo a clinical and radiologic examination. Outcome measures were implant and FPD failures, biologic and prosthetic complications, and marginal bone loss. Results: A total of 107 out of 127 patients attended the examination: 49 (113 implants) of the NDI group, and 58 (126 implants) of the SDI group. Two NDIs failed in one patient versus four SDIs in four patients ( P = 0.37). One FPD failed in the NDI group versus two FPDs in the SDI group ( P >0.99). Nine biologic complications occurred in the NDI group and twelve in the SDI group ( P = 0.81). Twelve prosthetic complications occurred in the NDI group and only two in the SDI group ( P = 0.001). Peri‐implant marginal bone loss at 5 years was 0.95 ± 0.84 mm for the NDI group and 1.2 ± 0.86 mm for the SDI group ( P = 0.06). Conclusion: Five‐year data indicate that FPD treatment in posterior mandibular and maxillary jaws with NDIs was as reliable as with SDIs, although NDIs showed a higher risk of prosthetic complications.